Dampak Urbanisasi Dalam Kehidupan Masyarakat Kota - Solu Nor Amaya; Altharik Mubarak; Reza Mauldy Raharja (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
In this article, the impact of urbanization on the lives of the people of Serang City is discussed. This article identifies various impacts due to urbanization through research and analysis carried out. Urbanization in Serang City affects many aspects of community life and the environment. One of the main effects of urbanization in Serang City is changes in land use. Green spaces and agricultural land have been converted into housing, shopping centers, offices and other urban infrastructure. Thus, productive agricultural land is reduced, biodiversity is lost, and environmental damage occurs. With economic growth and development of urban infrastructure, public services, and access to education, urbanization increases employment opportunities for local residents. However, urbanization also brings social and lifestyle changes, which can influence cultural values, daily habits, and social interaction patterns. With demand for housing increasing and a shortage of affordable housing. Apart from that, changes that occur in urban infrastructure and the impact they have on infrastructure access and traffic must also be considered. The method in this research uses qualitative interview techniques. By gaining a better understanding of these impacts, it is hoped that sustainable solutions can be developed to exploit the positive potential of urbanization and overcome the problems faced by the people of Serang City.